Exploring the Impact of AI-Driven Mobile Learning Platforms on Student Engagement and Academic Performance in Higher Education - Mabrouk, Sherin Hassan (Journal of Posthumanism, 2024)
This study examines the impact of AI-driven mobile learning platforms on student engagement and academic performance in higher education through a systematic review of recent literature. As interactive mobile technologies continue to reshape digital learning, artificial intelligence has emerged as a key driver of personalization, adaptive support, and real-time instructional responsiveness. Drawing on peer-reviewed studies published primarily between 2022 and 2025, this review synthesizes current evidence on how AI-supported mobile learning environments influence students’ learning experiences and academic outcomes. The analysis focuses on major AI-enabled functionalities, including adaptive learning systems, intelligent tutoring, learning analytics, and personalized feedback. Across the reviewed literature, these features are consistently associated with stronger behavioral, cognitive, and emotional engagement, particularly when mobile learning environments are designed to support flexibility, accessibility, and continuous learner interaction. The findings further suggest that the impact of AI on academic performance is largely indirect, operating through its capacity to enhance engagement, self-regulation, and sustained participation. Using a thematic synthesis approach, the study identifies recurring patterns, conceptual relationships, and contextual factors that shape the effectiveness of AI-driven mobile learning platforms. The review also highlights key moderating influences, including digital literacy, mobile usability, instructional design quality, and institutional readiness, all of which affect how learners benefit from AI-supported systems. As a secondary review, this study is based exclusively on published academic sources and does not involve human participants or primary data collection. The findings contribute to a clearer understanding of how AI-driven mobile learning platforms support student engagement and academic performance and offer evidence-based insights for the pedagogically grounded and ethically responsible integration of interactive mobile technologies in higher education.